SIMPLIFIED MEASUREING METHODS OF STRESSED-DEFORMED STATE OF AN EXPANDABLE SHELTER - D. V. Mishuta; V. G. Mikhailov (Приборы и методы измерений)
The developed original methodology is designed for testing van containers for cross-section and longitudinal sidesway typical in normal operation and does not require implementation of high cost equipment, devices, massive base or plates. The offered loading pattern and test methodology is highly cost effective, e.g. with minimum expenses it is possible to estimate the structural behavior of van containers, which is crucial for their development, manufacture and operation and makes it possible to hold trials at the enterprise, aimed at improvement of non-cargo container design.